Analisis Makna Motivasi Dalam Lirik Lagu “Dreamers” Karya Jungkook dan Fahad Al Kubaisi - Zenith Betanissa (Publikasi Indonesia, 2022)
Communication from time to time continues to experience development, starting from the use of smoke signals, drums, the invention of paper, the telegraph, telephone, computer, e-mail to a song. Teenagers in Indonesia today are very fond of watching and following boy bands from Korea. One of them is the character Jungkook. Especially now that the 2022 FIFA World Cup is being held which invites one of the Korean boy band personnel, Jungkook who sings with Fahad Al Kubaisi where he sings a song called